Clinical Characteristics and Visual Outcomes of Patients Hospitalized for Ocular Trauma in Shandong Province, China. (15th April 2020) - Duan, Fangnan; Chen, Xiunian; Zhang, Sai; Qi, Xiaolin; Shi, Weiyun; Gao, Hua
Abstract : Purpose . To analyze the clinical characteristics and visual prognoses of patients with ocular trauma treated in Shandong Eye Hospital. Methods . The inpatient data of patients with eye injuries hospitalized in our institution from January 2014 to December 2018 were retrospectively reviewed, including demographic information, types of trauma, causes of injury, treatment, and initial and final visual acuities. Results . A total of 1, 425 patients (1, 622 eyes), aged 39.5 ± 18.5 years, were included. The ratio of male to female was 5.3 : 1. Of the mechanical eye injuries, there were 490 (34.4%) open-globe injuries and 454 (31.9%) closed-globe injuries. Nonmechanical eye injuries had 426 patients (29.9%), while 55 patients (3.9%) had adnexal injuries. Over a half of the traumas were work-related (51.1%, 728 patients). Most patients were treated with surgical intervention (1, 404 eyes, 87.9%). There were significant differences in the final visual acuities between open-globe injuries and closed-globe injuries (P < 0.001 ), as well as between mechanical injuries and nonmechanical injuries (P < 0.001 ). The final visual acuity was closely correlated with the initial visual acuity (Spearman's correlation coefficient = 0.618, P < 0.001 ) and the OTS score (Spearman's correlation coefficient = 0.691, P < 0.001 ). Conclusion . Ocular trauma usually occurs in young and middle-aged men and in the workplace in Shandong Province. The proportion of nonmechanical injuries is high, and the prognosis is poor. A comprehensive understanding of the characteristics of ocular trauma is useful for blindness prevention and treatment.